Desenvolvimento de simuladores bioeconômicos para pisciculturas de terminação e reprodução de tilápia (Oreochromis niloticus) e determinação do índice de seleção da décima geração melhorada - ROSIANE ARAUJO RODRIGUES (2021)
Tilapiculture has featured prominently in national production. Many regions of the country have become productive centers, encompassing all the steps necessary for the production of tilapia. Due to its importance, the work was conducted with the objective of developing bioeconomic simulators for breeding and finishing fish farms, enabling the study of economic, technical, and financial variations of some simulated scenarios. After completing this step, the simulator was used to determine economic weights for finishing fish farms, having as a database information regarding the tenth generation of improved tilapia and thus achieving the selection index for characteristics of economic interest Body Weight at Slaughter (BWS) and Fillet Yield (FY) in the termination of tilapia. In the first study, a bioeconomic simulator for tilapia termination was developed, testing its efficiency in four production scenarios: monophase in tank-net (MonoT), monophase in nursely (MonoN), multiphase in tank-net (MultiT) and multiphase in nursely (MultiN). After the economic evaluation, all systems showed positive results. The MultiT system presented the highest Revenue (US$ 984,762.36) and Net Income (US$ 508,906.32), with productivity of 397.72 kg/m³/year. Financially, the MultiT system showed the best results, with an Internal Rate of Return (IRR) of 76.58% and a two-year payback. In the second study, a bioeconomic simulator was designed for breeding fish farms and tested in two scenarios: scenario 1 with reproduction in hapas and egg collection in the oral cavity of the matrix and scenario 2 with reproduction in nurseries and collection of post-larvae clouds. In the Statement of Economic Results (SER), Scenarios 1 and 2 presented Revenue US$ 122,764.17 and US$ 79,579.72, respectively, Total Cost US$ 103,181.35 and US$ 73,373.80, and Net Income of US$ 19,582.81 and US$ 6,205.92. Among the financial indicators contained in the simulator, scenario 1 and 2 presented a benefit/cost ratio (BCR) of 1.11 and 1.01, profitability index (PI) 1.48 and 1.04, IRR 17.82 and 8.95%, Net Present Value (NPV) US$ 81,655.54 and US$ 6,003.37 and payback for 6 and 10 years respectively. The third study, using the bioeconomic simulator for finishing fish farms, determined the economic weights of the BWS and FY characteristics so that they could be used in the composition of an economic selection index. The following were calculated using the bioeconomic simulator: economic value, genetic standard deviation, and genetic-economic value for the BWS and FY traits. The economic weights for BWS and FY in multiphase systems were US$ 4.828/10g and US$ 0.020/% respectively, higher than the values obtained in monophase systems (US$ 2.414/10g for BWS and US$ 0.012/% for FY). In tank-net, genetic-economic values are higher than those found in nursery, where in the present study they were 0.031 for BWS and 0.116 for FY. In all analyzed systems, the FY characteristic presented economic importance superior to the BWS, confirming its importance in the profit composition. In all studies, the bioeconomic simulator was able to present results close to those found in real situations in finishing and reproduction fish farms. Still other productive combinations, real or simulated, can be used. The simulator was able to determine the economic weights with which it was possible to develop the selection index for nursery and tank-net production systems.